The Policy and Politics of Influencing Interbreeding to Increase Population during the Regime of General Phibun and Its Unintended Consequence on the Status of Thai Women - Posrithong, Natanaree (Journal of Population and Social Studies [JPSS], 2020)
The aim of this paper is to explore the population policy during the regime of General Phibun and the political and social implications of government campaigns which actively sought to increase population. The policy was introduced in Thailand after the Second World War and was influenced by the theory of eugenics as well as a sense of urgency in advancing a radically different population policy. General Phibun, the Prime Minister of Thailand from both 1938 to 1944 and 1948 to 1957 carried out a number of salient social reforms that impacted women both positively and adversely in significant ways. Following the establishment of the Ministry of Health in 1942, the government implemented a policy to increase population, especially among certain sectors of society, as a primary policy agenda. With this salient aim of increasing population, the Organization for Marriage Support was founded as one of the agencies which used specific incentives to get healthy couples to marry and have children. Based largely on available official announcements and public records from the 1940s, this paper will discuss the mobility and status of middle-class women as they became subjects of the government’s policy on population.